Sustainable Islamic Tourism: Jogokariyan Ramadan Village as a Sustainable Religious and Economic Tourism Destination (Case Study in Jogokariyan Ramadan Village) - Wibowo, Wahyu; Choiri, Ahmad; Aminuddin, Aminuddin; Emilda, Puri; Salim, Fuad (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
Islamic tourism has gained significant attention as a driver of community-based economic development, with mosques playing a central role in religious, social, and economic activities. One notable example is Jogokariyan Ramadhan Village (JRV), an annual program that attracts thousands of visitors through religious events and MSME-driven markets. This study aims to analyze the sustainability of JRV in economic, social, and environmental aspects as a community-based religious and economic tourism destination. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and document analysis. Respondents included mosque managers, MSME actors, and tourists, with data analyzed using qualitative descriptive techniques based on the Triple Bottom Line model (economic, social, and environmental). The findings indicate that JRV has successfully improved the local economy through active MSME participation and transparent mosque fund management. Socially, JRV fosters strong community cohesion through mutual cooperation and empowerment initiatives. However, challenges persist, including a decline in economic activity after Ramadan and the environmental impact of market waste. The study underscores the importance of mosque-based economic initiatives in sustaining local businesses beyond Ramadan, demonstrating how religious tourism can be a catalyst for long-term economic resilience. Additionally, it highlights the need for improved waste management strategies to mitigate the environmental impact of large-scale religious events. To address these challenges, this study recommends strategies for economic diversification, the digitalization of MSME marketing, and the optimization of social programs to extend JRV’s positive impact throughout the year. By implementing these measures, JRV can serve as a model for sustainable religious tourism that can be replicated in other regions.